2004
DOI: 10.1111/j.1445-5994.2004.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion stings in Australia: five definite stings and a review

Abstract: Despite scorpions being locally abundant in many parts of Australia, scorpion sting is a poorly defined clinical condition in Australia. Many health-care workers are unaware of the effects of their stings and scorpions are often feared based on their international reputation. Five scorpion stings that occurred in different parts of Australia where the scorpion was caught at the time of the sting and identified by a professional arachnologist are reported in the present paper. The spectrum of clinical effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…For terrestrial envenomations, hot-water immersion was less commonly recommended (Table 5) [74,75,76,77,78], although there has been some support for the use of targeted, localized heat in the treatment of insect bites and stings [79]. Heat therapy is specifically contraindicated for recluse spider envenomations ( Loxoceles spp.…”
Section: Hot-water Immersion For Other Envenomationsmentioning
confidence: 99%
“…For terrestrial envenomations, hot-water immersion was less commonly recommended (Table 5) [74,75,76,77,78], although there has been some support for the use of targeted, localized heat in the treatment of insect bites and stings [79]. Heat therapy is specifically contraindicated for recluse spider envenomations ( Loxoceles spp.…”
Section: Hot-water Immersion For Other Envenomationsmentioning
confidence: 99%
“…Four studies reported envenomation, however Stern et al (2000), and Roll and Schmid-Grendelmeier (2005) reported that the entomologists in their studies were allergic to the venom, hence these have been classified as allergies. Bush et al (2001) and Isbister et al (2004) did not specify the type of reaction, and have therefore been classified as unspecified venom reactions. The majority of the included studies (n¼ 42) addressed allergies.…”
Section: Resultsmentioning
confidence: 99%
“…Allergy: Calliphora vomitoria (Diptera), Aphomia sociella (Lepidoptera), Tenebrio molitor (Coleoptera) and Hypopta agavis (Lepidoptera) Symptoms: Asthma, urticaria, and rhinoconjunctivitis Isbister et al (2004) 1990-2000s entomologists who had reported these symptoms. Wearing masks (Kaufman et al, 1986;Solley and Hyatt, 1980) and other forms of protective clothing (Monk 1988) reportedly helped in some cases.…”
Section: Occupational Management Of Adverse Work-related Health Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…In Spain, less than 1% of the scorpion stings can be regarded as severe and no deaths have been recorded [18]. Scorpionism is low in Australia too; the stings from Australian buthid scorpions have more severe effects than those from the larger species in the Urodacidae (genus Urodacus) and Liochelidae (genus Liocheles) families [155]. In the United States, deaths from scorpionism are extremely rare [17,18].…”
Section: Scorpions -Basic Epidemiologic Data and Main Control Effortsmentioning
confidence: 99%